Korelasi antara Pengetahuan, Sikap, dengan Perilaku Kepedulian Lingkungan Peserta Didik Kelas VIII SMP Negeri di Kota Makassar - Faezal Tanjung (Universitas Negeri Makassar, 2018)
This study aims to determine the magnitude of the value of Environmental Knowledge, Attitudes of Environmental Concern, and Behavior of Student Environment Concern Class VIII SMP Negeri in Makassar City, as well as the relationship between these variables. Data collecting was done by Cluster Random Sampling method and questionnaire of three variables involved in the scope of Makassar City namely SMP Negeri 5 Makassar, SMP Negeri 8 Makassar, SMP Negeri 13 Makassar, SMP Negeri 18 Makassar and SMP Negeri 25 Makassar. Data processing is done by doing descriptive analysis to describe character of each variable and inferential analysis to know the relation between knowledge and attitude variable with environmental awareness behavior along with correlation of affection. The result of this study indicates that there is a significant correlation between knowledge and attitude of environmental awareness with environmental awareness behavior of students of class VIII SMP Negeri in Makassar City. It is expected that the next researcher will involve other variables that are likely to influence the attitude and behavior of environmental awareness of learners such as social environment, culture, informal education.